The Effectiveness of Social Story Interventions Presented With the Orff Approach in Acquisition of Musical Skills by Developmentally Disabled Children - Dogan, Didem Mutlu Karsiyakali; Deniz, Jale; ÖZEN, ARZU (Education Association of South Africa, 2025)
In this study the effectiveness of social story (SS) interventions combined with the Orff approach in teaching musical skills to children with developmental disabilities (DD) was examined. Three middle school children - 2 girls and 1 boy with DD between 11 and 13 years old participated in the study. In this research, a single-subject with multiple-probe design with probe trials across subjects was employed. The research findings demonstrate that SS interventions combined with the Orff approach play an effective role in acquiring musical skills in children with DD. The results also show that all children could maintain and generalise their acquired musical skills. Finally, children and their families' opinions about the social validity were positive.
Keywords: Developmental Disability; Inclusion; Musical Skill; Orff Approach; Social Stories